Barriers and facilitators for adolescent girls to take on adult responsibility for dental care – a qualitative study. Issue 1 (1st January 2019) - Fägerstad, Anida; Lundgren, Jesper; Arnrup, Kristina; Carlson, Eva
ABSTRACT: Purpose : This study aims to explore and describe experiences of the dental care system among adolescent dental patients with a recent history of missed dental appointments at public dental clinics (PDCs) in a Swedish county. Methods : Twelve adolescent girls participated in the study. Data were collected by individual, semi-structured, open-ended interviews and analysed with qualitative content analysis. Results : The study findings could be summed into the theme "Triggers for adolescent girls to take on or not take on adult responsibility for dental care". The experience of free dental care could be summarized in five main categories: Pain and discomfort; Attractive and healthy teeth; Feeling safe and secure; Taking on the responsibility; and Free of charge. These five categories consisted of 15 subcategories. Conclusions : The results of this study should increase the knowledge on how to meet and treat adolescent girls in dental care. Knowing what will happen during the dental visit was highlighted by the participants as decisive to whether or not they would attend their dental appointments. Therefore, we should as far as possible ensure that our patients feel safe at their dental visits and by trying to avoid painful treatments.